Response Surface Methodology for Oxidative Degradation of the Basic Yellow 28 Dye by Temperature and Ferrous Ion Activated Persulfate - Gozmen, Belgin; Sonmez, Ozgur; Turabik, Meral (Asian Journal of Chemistry, 2013)
The decomposition of the persulfate by Fe2+ ions results in the production of oxidative sulfate radical anions. In present study, the oxidative degradation of the basic yellow 28 dye solution was studied by using persulfate and ferrous ions. To obtain maximum mineralization efficiency for aqueous solution of basic yellow 28, Box-Behnken design combined with response surface modeling (RSM). Four independent variables, namely temperature (40-70 ºC), initial concentration of persulfate (4-12 mM), ferrous ion (1-3 mM) and time (2-8 h) were transformed to coded values. Subsequently, it was determined that quadratic model to be the most suitable models to estimate the responses. Analysis of variance (ANOVA) was carried out for quadratic model and was observed the significance of the independent variables and their interactions. The predicted values of the oxidative degradation efficiency were verified to be in good agreement with the experimental values (R2 = 0.9902 and R2adj = 0.9804). Maximum mineralization efficiency 93 % was obtained under following conditions: persulfate concentration 9.87 mM, ferrous ion concentration 1.95 mM, temperature at 65 ºC and time at 8 h for 40 mg/L basic yellow 28 aqueous solution.